-4x+(x-3)(x+2)=0

Simple and best practice solution for -4x+(x-3)(x+2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+(x-3)(x+2)=0 equation:



-4x+(x-3)(x+2)=0
We multiply parentheses ..
(+x^2+2x-3x-6)-4x=0
We get rid of parentheses
x^2+2x-3x-4x-6=0
We add all the numbers together, and all the variables
x^2-5x-6=0
a = 1; b = -5; c = -6;
Δ = b2-4ac
Δ = -52-4·1·(-6)
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{49}=7$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-7}{2*1}=\frac{-2}{2} =-1 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+7}{2*1}=\frac{12}{2} =6 $

See similar equations:

| 90=-20(1+2x)+18x | | 2x+18=(-4x•18)+149350 | | (r÷4)-3=7 | | (r÷4-3=7 | | 4=-1+1-x+8 | | -2x+13-7x=-41 | | -3=9+x-7 | | 16x-3=-67 | | (x+1)(4-x)=6x | | -x/3+5=0 | | 5x^2-100x+95=0 | | X=4w+7 | | -4d+9=-39 | | .33(x+5)=2 | | -15=-4v-3 | | 24=1+1/4p | | 3/4r+4=13 | | 3-4(4-2x)=0 | | 5/9n-13=27 | | 3-7(8x+2)=9 | | (2x-5)(x^2+4x-5)=0 | | 10n-0.375=0.1n-0.75 | | 5h+16-7h-8=32 | | 7-7v=-56 | | 6x-48=-6 | | 42/x=54/100 | | 6x-6=-72 | | -4b-6=50 | | 4/3=m/3/5 | | 5m-2=58 | | P2+q=27 | | 6x-18=-48 |

Equations solver categories